Dados saúde: desenvolvimento de um aplicativo para gerenciar informações pessoais de saúde - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This paper describes the development of the Health Data application, an innovative solution for managing personal health information. The main goal of the project was to create an intuitive and user-friendly interface that would allow users to conveniently store, access, and manage their health information. Using Flutter’s technology, advanced functionality was developed that enabled an enhanced user experience. In addition, user surveys, usability testing, and collection of feedback were conducted to ensure the effectiveness and usability of the app. The results showed that the Health Data app met expectations, providing users with an efficient and secure way to manage their health information. The positive feedback from users confirmed the intuitive interface and ease of use of the app. In the future, the app is expected to be improved and extended to meet the evolving demands of users, providing an even more complete and comprehensive experience in managing personal health information. Keywords: Health; Application; Development.
Keywords: Engenharia de software; Saúde; Aplicativos móveis - desenvolvimento; Mobile apps; Health; CNPQ::CIENCIAS EXATAS E DA TERRA